The microstructure and magnetic characteristics of Sm(CobalFe0.1Cu0.09Zr0.03)7.24 high temperature permanent magnets. (15th April 2017) - Yu, Nengjun; Zhu, Minggang; Fang, Yikun; Song, Liwei; Sun, Wei; Song, KuiKui; Wang, Q.; Li, Wei
Abstract: Two kinds of Sm(Cobal Fe0.1 Cu0.09 Zr0.03 )7.24 high temperature magnets were fabricated by a traditional powder metallurgical technology with different annealing processes. A record of maximum energy product of 94.73 kJ/m 3 at 773 K with a high intrinsic coercivity of 652.72 kA/m was made. Based on the theoretical and experimental results, it was found that the temperature coefficient of the coercivity was strongly influenced by the variation of the Curie temperature of the cell wall phases and the domain wall energy ratio between cell and cell wall phases at 0 K. The characteristic properties originate from the element redistribution between SmCo5 /Sm2 Co17 interfaces while annealing. Graphical abstract: The temperature dependence of the coercivity of the Sm(Cobal Fe0.1 Cu0.09 Zr0.03 )7.24 high temperature magnets prepared by a traditional powder metallurgical technology with different annealing processes was analyzed, as shown in Fig. 1. Fig. 1(a) shows three H c ( T ) curves for 2 μ 0 c K II / c J II   = 26.1 T, 2 μ 0 c K I / c J I   = 1.25 T, ε KA  = 0.25 ± 0.05, ε AJ  = 1.8, T c cell  = 1093 K, T c wall  = 920 ± 50 K and the critical exponent ξ  = 0.365. Fig. 1(b) shows the temperature dependence of the type-A magnet with a higher Cu content in the cell wall and the superposition of all three analytical curves in Fig. 1(a). Fig. 1(c) shows three H c ( T ) curves for 2 μ 0 c K II / c J II   = 26.1 T, 2 μ 0 c K I / c J I   = 1.25 T, ε KA  = 0.4 ± 0.1, ε AJ  = 1.8, T c cell  = 1093 K, T c wall  = 940 ± 60 K and the critical exponent ξ  = 0.365. Fig. 1(d) shows the temperature dependence of H cj of the type-B magnet with a lower Cu content in cell wall phase and the superposition of all three analytical curves in Fig. 1(c).